Conceptual design of hybrid bio-composite for automotive bumper beam - Makinejad, Majid Davoodi; Salit, Mohd Sapuan; Ahmad, Desa; Ali, Aidy; Abdan, Khalina (2009)
Application of natural fiber composite is going to increase in different area due to environmental, technical and economical advantages; however their low properties limit their usage in automotive structural components. Contribution with other material as reinforcement, matrix and cooperation with other manufacturing method could improve mechanical properties. Moreover, product geometrical optimization could help to get better structural strength to overcome the product design specification (PDS) requirements. In this paper, conceptual design of hybrid natural fiber composite bumper beam is presented. The mechanical properties of developed hybrid composite material measured and considered in different bumper beam cross sections with the same curvature, thickness, length and width under the same impact process simulation standard in the Abaqus software in order to find the best cross section that withstand the impact load and absorb more energy during deformation. The double C channel presented the best one among others; however it has to modify by other parameters to comply the defined PDS.